Is structural connectivity different in child and adolescent relatives of patients with bipolar disorder? A narrative review according to studies with DTI (2023)
ABSTRACT: Introduction: Bipolar disorder (BD) has been associated with a decrease in white matter integrity. Diffusion tensor imaging (DTI) studies have enabled these changes to be elucidated with higher quality. Due to BD's high heritability, some studies have been conducted in relatives of BD patients looking at white matter integrity, and have found that structural connectivity may also be affected. This alteration has been proposed as a potential BD biomarker of vulnerability. However, there are few studies in children and adolescents. Objective: To conduct a review of the literature on changes in white matter integrity determined by DTI in high-risk children and adolescents. Results: Brain structural connectivity in the paediatric population is described in studies using DTI. Changes in the myelination process from its evolution within normal neurodevelopment to the findings in fractional anisotropy (FA) in BD patients and their high-risk relatives are also described. Conclusions: Studies show that both BD patients and their at-risk relatives present a decrease in FA in specific brain regions. Studies in children and adolescents with a high risk of BD, indicate a reduced FA in axonal tracts involved in emotional and cognitive functions. Decreased FA can be considered as a vulnerability biomarker for BD.